Proceedings of 2011 International Symposium on VLSI Technology, Systems and Applications 2011
DOI: 10.1109/vtsa.2011.5872255
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the mobility reduction in bulk-Si, UTBOX-FDSOI and SiGe devices with ultrathin-EOT dielectrics

Abstract: The effects of ultrathin EOT on the carrier mobility in bulk-Si, UTBOX-FDSOI and SiGe-QW pFET devices were compared. The mobility is found to decrease dramatically with the EOT (T inv ) as a result of stronger charge and surface roughness scattering at thinner SiO x interface layers irrespective of the device technology. UTBOX-FDSOI and bulk-Si nFETs have identical mobility values (190 cm 2 /Vs) at T inv =12.5Å. In the UTBOX-FDSOI device architecture, a positive back gate bias provides a strong enhancement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Thanks to an excellent electrostatic control and transport properties, this architecture is suitable to reach ITRS requirements for 28 nm technology node and beyond [4].The threshold voltage can be easily adjusted by applying back biases (VB) and it has recently been demonstrated that the mobility can be enhanced in the forward regime (VB > 0 V for nMOS and VB < 0 V for pMOS) [5]. However, the presence of high-k dielectrics can induce mobility degradations when the Interfacial Layer (IL) Equivalent Oxide Thickness (EOT) is decreased [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to an excellent electrostatic control and transport properties, this architecture is suitable to reach ITRS requirements for 28 nm technology node and beyond [4].The threshold voltage can be easily adjusted by applying back biases (VB) and it has recently been demonstrated that the mobility can be enhanced in the forward regime (VB > 0 V for nMOS and VB < 0 V for pMOS) [5]. However, the presence of high-k dielectrics can induce mobility degradations when the Interfacial Layer (IL) Equivalent Oxide Thickness (EOT) is decreased [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, scaling of the equivalent oxide thickness (EOT) in SiO x /HfO 2 dielectric stacks relies on reducing the physical thickness of the IL, which can be achieved in a controlled way by means of scavenging techniques [2], [3]. However, reducing the thickness of the IL has been shown to cause degraded mobility [4], [5], threshold voltage control [6] and reliability [7], severely limiting the scalability of SiO x interfacial layers below 0.4 nm.…”
Section: Introductionmentioning
confidence: 99%
“…However, the equivalent oxide thickness (EOT) scaling generally induces dramatic mobility degradation [5]- [7]. MOSFETs with FDSOI architecture and sub-1 nm or ultrathin EOT (UTEOT) are interesting because they lead to a device with high C INV and high mobility, but they also present a real challenge [8]. In this paper, we first investigate the mobility improvement resulting from the back bias for FDSOI with ultrathin-body and buried (UTBB) oxide devices with 0.8-nm EOT and compare it with SiON devices, using the direct extraction of the FC and BC mobilities, for several back (V B ) and front (V G ) gate biases.…”
Section: Introductionmentioning
confidence: 99%
“…The gate dielectric used is either 1.8-nm HfO 2 or 2.5-nm SiON. In both cases, the gate electrode consists of 5-nm TiN capped with poly-Si cap [8], [9]. The BG doping is about 10 17 cm −3 .…”
Section: Introductionmentioning
confidence: 99%